Electronic Interventions for Changing Knowledge, Attitudes or Practices Regarding Contraception: A Systematic Review. Issue 9 (September 2019) - Dewart, Courtney M.; Serpico, Jaclyn; Steiner, Markus J.; Gallo, Maria F.
Abstract : (Abstracted from Contraception, https://doi.org/10.1016/j.contraception.2019.04.004) Globally, nearly half of pregnancies are unintended. Sociodemographic factors associated with unintended pregnancy include age, parity, education, and economic status.